HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL DENGAN KEPATUHAN IBU MELAKSANAKAN IMUNISASI TETANUS TOXOID DI WILAYAH KERJA PUSKESMAS TANJUNG BALAI KABUPATEN KARIMUN TAHUN 2017 - Kristeti, Helen; Batubara, Saiful (Universitas Batam, 2018)
Tetanus neonatorum is one of the leading causes of infant mortality in Indonesia which has arisen as a result of low coverage of antenatal care and TT immunization. Based on data from Tanjung Balai Community Health Clinic 2017 that visit of K-1 expectant in February as many as 80respondents and March 89 visits, but there was a decline in April that was only 83 visits. This research is a research in the form of analytic survey with cross sectional study design. The method used was accidental sampling obtained 56 respondents. Data collection was by using questionnaire and conducted in June 2017. From the statistical chi square test obtained p value = 0,000 which means the value of p value is smaller than 0,05 (0,000 <0,05). Thus Ho is rejected, this indicates that there is a correlation between the knowledge level and the compliance of TT immunization during pregnancy. The result of chi square statistical test is obtained p value = 0,001 meaning p value is smaller than 0,05 (0,001 <0,05). Thus Ho was denied, this indicated that there is a correlation between the respondents' attitude with expectant obedient to implement TT immunization during pregnancy in Karimun District KarimunÂ